The role of microRNAs in skin cancers - Nature Research (16552612) (2015)
Skin cancer is a growing public health problem around the world, largely due to an aging population and increased exposure to ultraviolet radiation in sunlight, which causes more than 90% of all cases. In the past decade or so, a class of molecules called microRNAs has been implicated in the development of skin cancers. A literature review by Rebecca Ruland and Ana-Maria Florea of the University of Trier summarizes what is known about their role in basal cell carcinoma and squamous cell carcinoma, two common benign forms of skin cancer . MicroRNAs are encoded in the genome but do not code for any proteins, instead they regulate gene expression within the cells. They are between 20 and 25 nucleotides in length, and function by binding to messenger RNA transcripts and preventing them from being translated into functional protein molecules. MicroRNAs can contribute to the development of cancer by inhibiting the expression of tumour suppressor genes, thus enhancing the expression of oncogenes. Indeed, expression of microRNAs themselves is altered in all types of tumours, compared to healthy tissues. Most research into the role of microRNAs has been done on brain tumours and breast cancer. While they are known to regulate skin development, scientists know little about their possible roles in skin cancer. One gene probably involved is called p53, it normally suppresses tumour growth by activating multiple genes that encode proteins involved in regulating DNA repair, progression through the cell cycle, and programmed cell death. “This area of research is just beginning and new microRNAs are still being discovered but their functions are unknown” says Florea. A handful of studies provide evidence that some microRNA molecules interact directly with the p53 protein. Others suggest that they play a critical role in regulating cancer patients’ sensitivity to chemo- and radiotherapy, and in the process by which tumours become resistant to anti-cancer drugs. Given these likely roles, microRNAs may prove to be useful markers for both the diagnosis and prognosis of skin cancers. Eventually, a better understanding of their role in skin cancer may also lead to ‘personalized’ anti-cancer treatments that are tailored to the individual. “We need to use all the tools we have to fight cancer, and microRNAs might be an important target for treating it in the future,” says Florea, adding that more funding to study these molecules could help answer the many questions still remaining. Other Information Published in: QScience.com Highlights, Published by Nature Research for Hamad bin Khalifa University Press (HBKU Press) License: http://creativecommons.org/licenses/by/4.0